Venetoclax consolidation after fixed-duration venetoclax plus obinutuzumab for previously untreated chronic lymphocytic leukaemia (HOVON 139/GiVe): primary endpoint analysis of a multicentre, open-label, randomised, parallel-group, phase 2 trial. Issue 3 (March 2022) - Kersting, Sabina; Dubois, Julie; Nasserinejad, Kazem; Dobber, Johan A; Mellink, Clemens; van der Kevie-Kersemaekers, Anne-Marie F; Evers, Ludo M; de Boer, Fransien; Koene, Harry R; Schreurs, John; van der Klift, Marjolein; Velders, Gerjo A; et al.
Summary: Background: Fixed-duration 12 cycles of venetoclax plus obinutuzumab is established as first-line treatment for patients with chronic lymphocytic leukaemia. We aimed to determine the activity and safety of 12 cycles of venetoclax consolidation after fixed-duration venetoclax plus obinutuzumab for previously untreated patients with chronic lymphocytic leukaemia who were unfit for fludarabine-based treatment, and whether this could be guided by minimal residual disease status. Methods: We conducted an open-label, randomised, parallel-group, phase 2 trial (HOVON 139/GiVe) at 25 hospitals in the Netherlands. Eligible patients were aged 18 years or older with previously untreated chronic lymphocytic leukaemia, had an ECOG performance status of 0–2, and were unfit for fludarabine-based treatment. All patients received two debulking cycles of intravenous obinutuzumab (100 mg on day 1, 900 mg on day 2, and 1000 mg on days 8, 15, and day 1 of cycle two), followed by fixed-duration venetoclax plus obinutuzumab for 12 cycles (six cycles of intravenous obinutuzumab 1000 mg on day 1 and 12 during 28-day cycles of oral venetoclax, starting with a 5-week ramp-up and then 400 mg once daily until completion of cycle 12). Patients were then randomly assigned (1:1) by minimal residual disease status in peripheral blood, to receive either 12 cycles of venetoclax consolidation irrespective of minimal residual disease or venetoclax consolidation only if minimal residual disease was detected at randomisation. The primary endpoint was undetectable minimal residual disease in bone marrow and no progressive disease 3 months after end of consolidation treatment (or corresponding timepoint) by intention-to-treat. Safety was assessed in all patients who received at least one dose of any study drug. This is the primary endpoint analysis of this trial, which is ongoing and is registered with EudraCT (2015-004985-27). Findings: Between Oct 28, 2016, and May 31, 2018, 70 patients were enrolled, of whom 67 (47 [70%] men and 20 [30%] women) received fixed-duration treatment and 62 were randomly assigned to receive 12 cycles of venetoclax consolidation (n=32) or minimal residual disease-guided venetoclax consolidation (n=30; one of whom was minimal residual disease positive at randomisation). Median follow-up was 35·2 months (IQR 31·5–41·3). 16 (50% [95% CI 32–68]) of 32 patients in the consolidation group and 16 (53% [34–72]) of 30 in the minimal residual disease-guided consolidation group met the primary endpoint of undetectable minimal residual disease in bone marrow and no progressive disease. 22 (69%) of 32 patients in the venetoclax consolidation group and 11 (37%) of 30 in the minimal residual disease-guided consolidation group had any adverse event (grade 2–4; mainly infections). The most common grade 3 or worse adverse events were infection (two [6%] of 32 patients in the consolidation group and one [3%] of 30 in the minimal residual disease-guided consolidation group) and neutropenia (two [6%] and two [7%]). There were no treatment-related deaths. Interpretation: Consolidation with venetoclax 12-cycle treatment increases the duration of known side-effects and does not prevent the loss of minimal residual disease response and subsequent risk of disease relapse. Funding: F Hoffmann-La Roche.